(untitled) (World Bulletin of Public Health, 2025)
Cardiovascular diseases (CVDs) remain one of the leading causes of mortality worldwide, demanding continuous innovation in therapeutic approaches. Recent advancements in molecular biology, pharmacogenomics, and biotechnology have contributed to the development of more effective and targeted drug strategies. These include personalized medicine, gene-based therapies, novel antithrombotic agents, antiinflammatory drugs, and compounds that improve endothelial function. Modern drug development also emphasizes reducing adverse effects and improving long-term patient outcomes. This paper highlights emerging pharmacological strategies aimed at preventing, managing, and treating cardiovascular diseases through innovative, evidence-based approaches